Pengendalian Persediaan Bahan Baku Menggunakan Metode Min-Max Stock - Abyan Thariq Fadhilah; Joumil Aidil Saifudin (Universitas Trunojoyo Madura, 2023)
The problem of planning and controlling inventory is one of the most important things that every company must face. This study aims to determine the description of raw material inventory management using Min-Max Stock at PT Delta Jaya Engineering and to determine the cost of inventory disbursed by using the Min Max Stock method. Data collection is preferred to use primary data from interviews and observations to the company. While the secondary data obtained from the company's historical data. The results of this study found that theoretically shows the minimum and maximum limit value of stock, safety reserve (safety stock), and the level of reorder (Q) is different for each raw material. In addition, by using the policy proposal with the minâ€“max stock method, the cost calculation results show that the costs incurred by the company each year are lower because there are no raw materials that are over stock or out of stock. Â